2014
DOI: 10.3389/fnhum.2014.00844
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality in Craving Assessment and Cue-Exposure Therapy in Substance Use Disorders

Abstract: Craving is recognized as an important diagnosis criterion for substance use disorders (SUDs) and a predictive factor of relapse. Various methods to study craving exist; however, suppressing craving to successfully promote abstinence remains an unmet clinical need in SUDs. One reason is that social and environmental contexts recalling drug and alcohol consumption in the everyday life of patients suffering from SUDs often initiate craving and provoke relapse. Current behavioral therapies for SUDs use the cue-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 101 publications
(157 reference statements)
5
123
0
1
Order By: Relevance
“…Several results suggest that immersing subjects in virtual environments related to an addiction can combat many issues regarding craving assessment (Hone-Blanchet et al, 2014;Pericot-Valverde et al, 2016). VR have proved to be effective in triggering craving in both substance use disorder and behavioral addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Several results suggest that immersing subjects in virtual environments related to an addiction can combat many issues regarding craving assessment (Hone-Blanchet et al, 2014;Pericot-Valverde et al, 2016). VR have proved to be effective in triggering craving in both substance use disorder and behavioral addiction.…”
Section: Discussionmentioning
confidence: 99%
“…It can be discussed that abstinence-induced and cue-induced craving may ultimately represent the same neurological phenomena, but works have demonstrated that in smokers, craving can be induced with cues a few minutes after nicotine smoking (Franklin et al, 2007), suggesting that cue-reactivity may work independently from pharmacological stimulation and abstinence state. Additionally, it is often proposed that cue-induced craving paradigms may be a more ecologically valid approach, as recuperating SUDs patients are sensitive to environmental drug-related cues (Ferguson and Shiffman, 2009; Hone-Blanchet et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…We focus here on craving because it is now a DSM 5 criterion for SUD. Craving is also considered a predictive factor of relapse following a quit attempt because of abnormal cue-reactivity in SUD patients (Baker et al, 2012; Goudriaan et al, 2010; Paulus et al, 2005; Hone-Blanchet et al, 2014) but this concept is still disputed (Perkins, 2012). For instance, in tobacco use disorder (TUD), it is suggested that therapies for smoking cessation should tune down cue-induced craving (Ferguson and Shiffman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The increased availability of VR technology helps address this limitation by providing an immersive and standardized context that can be systematically applied to activate and extinguish cigarette cravings [47]. The use of VR is supported by recent reviews and metaanalysis of computer-generated smoking environments which found robust craving effects in cue-reactivity research [47][48][49]. However, there are several limitations of traditional, computergenerated VR environments, including the time and technical expertise required to produce them, and the video game quality of the graphics, which have not yet achieved an optimal level of realism.…”
Section: Cue Exposure Protocol and Rationalementioning
confidence: 99%